A "Systematic Approach" to TD‐GPC Data Processing with Band Broadening Correction. Issue 1 (23rd August 2013) - Yau, Wallace; Brown, Ray; Tyler, Phillip; Huang, Tianzi; Cong, Rongjuan; Klinker, Chanda; Hazlitt, Lonnie; Soares, João B.P.
Summary The application of the systematic approach during detector offset determination in triple detector GPC polymer analysis has been shown to result in improvements in terms of the variations observed among the methods for molecular weight distribution determination. More importantly, the remaining, reduced variations are theoretically consistent with axial dispersion corrections proposed in the past. The use of the systematic approach for offset determination coupled with a robust axial dispersion correction offers the potential for completely reconciling the molecular weight results obtained from the three available methods of molecular weight determination in triple detector GPC.